Barnesiella intestinihominis improves gut microbiota disruption and intestinal barrier integrity in mice with impaired glucose regulation - Liu, Xiaojia; Wang, Ling; Huang, Bing; Jiao, Yi; Guan, Yaqun; Nuli, Rebiya (Frontiers in Pharmacology, 2025)
IntroductionImpaired glucose regulation (IGR) is a prediabetic state closely associated with gut microbiota dysbiosis. Our previous metagenomic analysis identified a significant deficiency of Barnesiella intestinihominis (B. intestinihominis) in IGR patients (p < 0.01). The present study was therefore designed to investigate the therapeutic potential of B. intestinihominis supplementation in a high-fat diet (HFD)-induced IGR mouse model and to explore its potential mechanisms of action.MethodsA mouse model of IGR was established by HFD. The treatment group received a daily supplementation of live B. intestinihominis (1×108 CFU) for 5 weeks. Gut microbiota composition was analyzed. Colonic expression levels of tight junction proteins (ZO-1 and occludin) and cytokines (IL-10, TNF-α, IL-6) were measured. In vitro experiments using Caco-2 human intestinal epithelial cells were conducted to assess the direct effects of B. intestinihominis. B. intestinihominis fermentation broth, heat-inactivated bacterial solution, and bacterial solution were co-cultured with Caco-2 cells. Cell viability was assessed using the CCK-8 assay, and the expression levels of tight junction proteins were evaluated. Trans-epithelial electrical resistance (TEER) and alkaline phosphatase activity were also assessed in the Caco-2 model.ResultsDaily supplementation with B.intestinihominis significantly attenuated HFD-induced hyperglycemia in mice. It also modulated the gut microbiota, evidenced by an increased abundance of beneficial Ligilactobacillus and a reduction in pathogenic Lachnoclostridium. Furthermore, B. intestinihominis administration upregulated the expression of colonic tight junction proteins (ZO-1 and occludin) and the anti-inflammatory cytokine IL-10, while simultaneously inhibiting the pro-inflammatory mediators TNF-α and IL-6. In vitro, the fermentation broth of B.intestinihominis (10%) increased Caco-2 cell viability, and heat-inactivated bacteria (1×107 CFU) enhanced ZO-1 expression. However, neither treatment significantly affected trans-epithelial electrical resistance (TEER) nor alkaline phosphatase activity in Caco-2 cells.DiscussionThese findings suggest that intestinal probiotics B. intestinihominis may ameliorate IGR by modulating the gut microbiota, enhancing intestinal barrier integrity, and attenuating inflammation, thus supporting their potential as a therapeutic intervention for metabolic disorders.